Pesan Moderasi Beragama M. Quraish Shihab dalam Channel Youtube Najwa Shihab Edisi Islam Wasathiyyah, Islam yang di Tengah - Jannah, Rosyada Roihatul; Slamet, Moh.; Suhari (Menara Tebuireng, 2023)
This study aims to analyze the message of religious moderation conveyed by M. Quraish Shihab on Najwa Shihab's YouTube channel with the theme of Wasathiyyah Islam, namely the Islamic concept that emphasizes the middle, balance, and tolerance. The purpose of this study is to explore a deeper understanding of how M. Quraish Shihab conveys messages of moderation in the context of the Islamic religion which are applied in everyday life. This research will use a qualitative approach with the Holsti theory content analysis method. The primary data sources obtained in this study were taken from YouTube video uploads of Najwa Shihab, Islam Wasathiyyah edition, Islam in the Middle and secondary data in the form of documents, books related to the object under study along with relevant previous research. Data collection techniques were carried out by observation and documentation as well as on data analysis techniques obtained from interviews, field notes and other materials. From the results of the analysis carried out by the researcher, the conclusion was in the form of a message of religious moderation conveyed by M. Quraish Shihab. As for the messages of religious moderation conveyed by M. Quraish Shihab on the Najwa Shihab Youtube channel, the Islam Wasathiyyah edition, Islam in the Middle is associated with the four pillars of religious moderation. The pillars include: Fairness, balance, tolerance and tawassuth. Keyword: Message of Religios Moderation, Content Analysis, M. Quraish Shihab, Youtobe Social Media